DIGITAL INNOVATIONS IN FAMILY LAW OF UKRAINE: LEGAL ANALYSIS OF THE FUNCTIONALITY OF THE PLATFORM “DIIA” AND ITS IMPACT ON THE EVOLUTION OF THE INSTITUTE OF FAMILY LEGAL RELATIONS - Diduk, Alla; Нerasymenko Oleksandra (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Objective: to determine the impact of digitalization on the development of family law relations in Ukraine by analyzing the innovations of the Diia application as a modern tool for digital transformation in the field of public services. To identify the advantages, challenges and prospects of using such digital technologies to simplify and improve legal relations in the field of family law. To explore the regulatory framework for the implementation of the transformation processes of the Diia platform. Research methods: Analysis and synthesis, comparative legal method, sociological method, empirical and prognostic methods. Results: a detailed overview of the functionality of the Diia platform in the field of family law. Identification of the benefits of digitalization in simplifying procedures and improving citizens’ access to services compared to traditional methods. Establishing the need to improve family law and other regulations to legitimize digital transformation processes. Discussion: the impact of innovative digital services on family law, in particular on legal relations between citizens and the State, the benefits and challenges associated with the introduction of digital tools in the field of family law, the prospects for using the latest technologies for further modernization of family law.